2023
DOI: 10.26599/nbe.2023.9290020
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Green Synthesis of Manilkara zapota Capped Silver Nanoparticles and Their Antimicrobial Application Through Formulation of Nano-gel Systems

Abstract: The present study is based on optimized green synthesis of silver nanoparticles (AgNPs) using Manilkara zapota fruit extract, formulation of topical gels, and evaluation for their antimicrobial properties. The results reveal that a reaction temperature of 35 °C and a reaction time of 11 h are the optimum conditions to get spherical AgNPs with a particle size of 100.7 nm and a zeta potential of −26.7 mV. The synthesized AgNPs formulated as topical gels demonstrate a broad-spectrum antimicrobial activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Parashar and Garg (2022) and Parashar and Garg (2023) reported that AgNPs synthesized by MZL possess significant antibacterial and antioxidant activity. 26,43 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Parashar and Garg (2022) and Parashar and Garg (2023) reported that AgNPs synthesized by MZL possess significant antibacterial and antioxidant activity. 26,43 …”
Section: Resultsmentioning
confidence: 99%
“…Parashar and Garg (2022) and Parashar and Garg (2023) reported that AgNPs synthesized by MZL possess signicant antibacterial and antioxidant activity. 26,43 3.7 Application of the determination of STR using AgNP-MZL in agricultural, environmental and soil samples To investigate the practicality of the established STR detection method, the recovery study of this green synthesized AgNP-MZL-based biosensor was performed in four types of real-water samples, including surface water, river water, tap water, sewage water, and river water (SW, TW, SGW, and RW), four types of soil samples (SR-1, SD-2, SR-3, and SB-4) and three types of agricultural samples, including potato (Ag-P), tomato (AgAg-T) and green beans (AgAg-G). An aliquot of ltered water/soil/agricultural sample (1.0 mL) was added into a glass vial containing 1 mL of green synthesized AgNP-MZL at pH 4.0.…”
Section: Effects Of Potentially Interfering Compounds and Crosscontam...mentioning
confidence: 99%
See 2 more Smart Citations